A Lactobacillus consortium provides insights into the sleep-exercise-microbiome nexus in proof of concept studies of elite athletes and in the general population - Tindaro Bongiovanni; Marina Santiago; Kinga Zielinska; Jonathan Scheiman; Carolina Barsa; Ralf Jäger; Daniela Pinto; Fabio Rinaldi; Giammaria Giuliani; Tullio Senatore; Aleksandar D. Kostic (Microbiome)
Abstract Background The complex relationship among sleep, exercise, and the gut microbiome presents a unique opportunity to improve health and wellness. Here, we conducted the first large-scale investigation into the influence of a novel elite athlete-derived probiotic, consisting of a multi-strain Lactobacillus consortium, on sleep quality, exercise recovery, and gut microbiome composition in both elite athletes (n = 11) and the general population (n = 257). Results Our two-phase study design, which included an open-label study followed by a controlled longitudinal study in a professional soccer team, allowed us to identify key interactions between probiotics, the gut microbiome, and the host. In the placebo-controlled study, we observed significant improvements in self-reported sleep quality by 69%, energy levels by 31%, and bowel movements by 37% after probiotic intervention relative to after placebo. These improvements were associated with a significant decrease in D-ROMS (a marker of oxidative stress) and a significantly higher free-testosterone/cortisol ratio. Multi-omics analyses revealed specific changes in microbiome composition and function, potentially providing mechanistic insights into these observed effects. Conclusion This study provides novel insights into how a multi-strain Lactobacillus probiotic modulates sleep quality, exercise recovery, and gut microbiome composition in both the general population and elite athletes, and introduces potential mechanisms through which this probiotic could be influencing overall health. Our results emphasize the untapped potential of tailored probiotic interventions derived from extremely fit and healthy individuals in improving several aspects of health and performance directly in humans. Video Abstract